Mayor Daan Mogot (1928-1946) Peran dan Perjuangannya - Permana, Rahayu (Universitas Indraprasta PGRI, 2021)
This study aims to determine the biographical study of the figure of Mayor Daan Mogot in Tangerang. Daan Mogot's biographical study approach is veryinteresting to research, because he was a very important figure during theIndonesian independence revolution in the Tangerang area. The researchmethodology uses a qualitative approach by collecting data sources relevant tothe discussion. The results of research on the role and struggle of Major DaanMogot include starting his career as a Map Army, BKR, TKR-TRI and becomingthe director of the Tangerang Military Academy. Major Daan Mogot's struggleneeds to be a good example for today's young generation. So that his heroic valuescan be an inspiration for the people of Tangerang in particular and in general theIndonesian people.Keywords: Biography, Daan Mogot, His Struggle